Promoter induced rapid synthesis of AlPO4-5 molecular sieve in non-aqueous media using hexamethyleneimine template - Venkatathri, N. (Journal of the Indian Chemical Society, 2006)
AlPO4-5 have been synthesized from non-aqueous media using hexamethyleneimine template in presence of sodium ions. The results show that the sodium catalyses the nucleation and crystallization process of the formation of AlPO4-5 molecular sieve. The material synthesized was characterized by XRD, SEM, carbon and nitrogen analysis, TG/DTA, FT-IR, Al-27 and P-31 MASNMR. The results show that the samples are highly crystalline. The presence of octahedral and tetrahedral sites are observed in 27 At MASNMR, P-31 MASNMR gives only a single peak for tetrahedral phosphorous atoms.
Keywords: aluminophosphates; Molecular sieve; non-aqueous media